Presidency of the Republic and Presidential Style in Colombia: between Personalism and Institutionalization in the Armed Conflict Context - de Araújo Filho, Valdemar F.; Rivas Otero, José Manuel (Revista del CLAD Reforma y Democracia, 2020)
This paper aims to discuss some of the political and institutional determinants behind the changes in the organization of the Colombian Presidency during the governments of Álvaro Uribe (2002-2010) and Juan Manuel Santos (2010-2018). To this end, it identifies to which extent the presidential style of each of these two presidents was manifested in the institutional and administrative changes experienced by the Presidency during the period studied. Government reform in Colombia is a unique case in Latin America. In a regional context where the priorities were market-oriented State reforms, the changes in the organization of the Colombian Presidency, carried out in the context of the internal armed conflict, have shaped a model that has provided the various governments with a strategic political base endowed with operational flexibility and administrative ramifications, avoiding the dismantling of structures already consolidated at the center of government.
Keywords: Head of Government; Presidential Office; Modernization o f High Government; Conflict Management; Conflict; Violence; Colombia